Identifikasi Lapisan Geologi Bawah Permukaan Berdasarkan Data Geomagnetik di Sungai Logawa Banyumas - Sukmaji Anom Raharjo; Sehah Sehah; Adi Candra (Dinamika Rekayasa, 2014)
Identification of geological resources can be done either using surface mapping and cross sectional stratigraphy measurement or geophysical approximation beneath the earth surface. Geomagnetic exploration related to the existing of gold mineral begins with the total magnetic field intensity measurements at 173 locations was scattered in 109.196970 - 109.207580E and 7.448830 - 7.454110S. Interpretation from processing of data obtained four anomalous object, which is defined as fine-medium sandstone (χ= 0.0015 cgs units), coarse sandstone and compact (χ= 0.0035 cgs units), igneous basalt-andesite old Slamet (χ= 0.0085 cgs units), and the complex bedrock (χ= 0.0145 cgs units). The presence of gold mineralization in the rock throughout geomagnetic surveys used to identification of subsurface geological which is interpreted from the processing data that indicated the presence of gold in association with sedimentary (sandstone) is often referred to as sediment-hosted.